Investigating the impact of time allocation on family well-being in China - Hong, Qianru; Jiao, Xukun; Qiu, Xiaohang; Xu, Aiting (Journal of Business Economics and Management, 2024)
This study aims to analyze the relationship between family time allocation patterns and subjective well-being of Chinese married women. Using the fixed-effect ordered logit model and data from CFPS 2014–2018, this study empirically explores the impact mechanism and heterogeneity of family time allocation patterns on married women’s well-being. The results indicate that the mode of working full-time and handling the majority of housework is an impact negatively for women, and this result is robust. Further heterogeneity analysis reveals that market work has a weaker impact on low-educated women’s well-being than housework, but this is reversed for high-educated women. In particular, the single-time poverty brought on by housework specifically reduces women’s well-being, more than that of dual-time poverty of work time and housework time. Also, the happiness efficiency resulting from women reducing housework time will increase with the rise in happiness levels. Accordingly, this paper highlights three policy implications: enhancing happiness effectiveness, optimizing family time allocation patterns, and raising women’s status. The conclusion clarifies the path to gender equality in family labor division and provides new recommendations for relevant nations on how to promote the equalized gender division of labor and enhance the standard of living for women.